Natural Resource Management in the Context of Climate Change - United Nations Conference on Trade; Development (United Nations, 2020)
The management of natural resources is directly associated with climate change. On the one hand, most of the greenhouse gases released in the atmosphere originate from the production, transformation and use of natural resources such as coal, natural gas and oil. On the other hand, climate change affects natural resources such as forests and agricultural produce. These interactions illustrate the two-way relationship between climate change and the commodities sector. This paper analyses the ways in which the management of natural resources may impact climate change, and how climate change impacts the adaptation strategies of countries, industries and farmers that extract or produce primary commodities. Resource management is analysed from the perspective of a capital conversion-based model of development. One important conclusion of the paper is that integrating climate change concerns into resource management implies that some natural resources will need to be stranded in order to meet mitigation commitments compatible with the goal of limiting global warming to well below 2 degrees Celsius and pursuing efforts to limit the increase in the average value of global temperature to 1.5 degrees Celsius above pre-industrial levels.